2002
DOI: 10.1097/00000421-200204000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Short-Term Survival and Progression to Chemotherapy in Patients With Advanced Colorectal Cancer Treated With 5-Fluorouracil-Based Regimens

Abstract: The aim of this study was to assess in patients with advanced colorectal cancer which factors were associated with short-term survival (6 months or less) and progression to first-line 5-fluorouracil (5-FU) chemotherapy. Three hundred twenty-one consecutive nonselected patients with advanced colorectal cancer were treated with conventional 5-FU-based regimens as first-line treatment from 1988 to 1999. Factors related to patient, tumor, or treatment were analyzed by univariate and multivariate logistic regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…Thus, different age ranges of the populations studied, or different age groups chosen for the analyses, together with a variable prevalence of nonneoplastic diseases in the evaluated series, can explain the discordant results in the scientific literature regarding age and colorectal cancer. Indeed, different authors have found an independent unfavourable effect of increasing age (Korenaga et al, 1991;Gasser et al, 1992;Crocetti et al, 1996;D'Eredita et al, 1996;Wolters et al, 1996;Payne and Meyer, 1997;Tominaga et al, 1997;Heys et al, 1998;Lagautriere et al, 1998;Fietkau et al, 2004;Munemoto et al, 2004), of the youngest and oldest age ranges, indifferently (Chung et al, 1998;Cerottini et al, 1999;Massacesi et al, 2002) or even of young age (Cai et al, 2005), while other investigators were not able to demonstrate any prognostic effect at all (Ponz de Leon et al, 1992;Wang et al, 2000;Mitry et al, 2004;Latkauskas et al, 2005). Only JanssenHeijnen et al (2005) evaluated relative survival of patients with several cancers, utilising data from the Southern Netherlands Cancer Registry.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different age ranges of the populations studied, or different age groups chosen for the analyses, together with a variable prevalence of nonneoplastic diseases in the evaluated series, can explain the discordant results in the scientific literature regarding age and colorectal cancer. Indeed, different authors have found an independent unfavourable effect of increasing age (Korenaga et al, 1991;Gasser et al, 1992;Crocetti et al, 1996;D'Eredita et al, 1996;Wolters et al, 1996;Payne and Meyer, 1997;Tominaga et al, 1997;Heys et al, 1998;Lagautriere et al, 1998;Fietkau et al, 2004;Munemoto et al, 2004), of the youngest and oldest age ranges, indifferently (Chung et al, 1998;Cerottini et al, 1999;Massacesi et al, 2002) or even of young age (Cai et al, 2005), while other investigators were not able to demonstrate any prognostic effect at all (Ponz de Leon et al, 1992;Wang et al, 2000;Mitry et al, 2004;Latkauskas et al, 2005). Only JanssenHeijnen et al (2005) evaluated relative survival of patients with several cancers, utilising data from the Southern Netherlands Cancer Registry.…”
Section: Discussionmentioning
confidence: 99%
“…Age was associated with survival duration in some studies, but the direction of effect was inconsistent. Most studies used a single cut-off between 60 and 70 years, which would be suitable for [31][32][33][34][35][36][37], breast [38,39], pancreas [44][45][46][47], urothelial [48,49,51,52], gastric [54], GI [55,56], oesophageal [58], prostate [59], melanoma [61], renal [63] Lung Trial outcome index=sum of physical well being, functional well being and lung cancer subscale of the FACT-L. Egogram=Tokyo University Egogram (scores 5 ego state factors: critical parent, nurturing parent, adult, free child and adapted child) UV Univariable analysis, MV multivariable analysis, KPS Karnovsky performance score, ECOG Eastern Cooperative Oncology Group performance score monotonic effects; for example, better survival in younger (or older) patients but would miss U-shaped relationships or if prognosis was better in typical middle-aged patients but worse in the youngest and oldest. Co-morbidity seems more important than age.…”
Section: Discussionmentioning
confidence: 99%
“…Formal meta-analysis was neither planned nor attempted because the populations, methods and reported results were too heterogeneous. [32][33][34][35], pancreas [44][45][46][47], urothelial [48,51,52], gastric [53,54], GI [55,56], oesophageal [58], renal [63] Male worse [31,33,34], breast [38,40], pancreas [43,44,46,47] , urothelial [48,51,52] gastric [53,54], GI [56], oesophageal [58], ovary [62], renal [63] Younger …”
Section: Methodsmentioning
confidence: 99%
“…CEA elevation correlates with the degree of tumor differentiation, and patients with poorly differentiated tumors can sometimes have normal tests despite significant tumor volume [31]. In general, however, CEA correlates with stage of disease and is elevated most strikingly in the plasma of patients with hepatic metastases [32, 33]. …”
Section: Discussionmentioning
confidence: 99%